Pengembangan Media Pembelajaran Video Animasi pada Materi Perubahan Lingkungan Siswa Kelas V SD - Adelia Pitri; Maharani Oktavia (Journal on Education, 2023)
The aim of the research is to develop an animated video learning media in order to determine the validity, practicality, and potential effects of the developed animated video media. The type of research used is Research and Development (R&D) with the ADDIE method which consists of analysis, design, development, implementation, evaluation. The results of the study The results of the development of instructional media in the form of animated videos were declared valid. This can be seen from the results of the assessment of media, material and language experts who obtained a percentage of 84% with Very valid criteria. Based on the value given by the validator, the animated video media can be declared valid for use in the learning process. The results of the development of the animated video were stated to be practical, this can be seen from the response from the educators, namely obtaining a percentage of 86.1% with the criteria "Very Practical", the response of students in the One-to-one trial obtained a percentage of 83% with the criteria "Very Practical". while the responses of students in small group trials obtained a percentage of 87% with the criteria of "Very Practical" based on the responses from educators and students, then animated video media can be stated to have practicality. The results of the development of animated videos were declared effective, this can be seen from the results of research on field trials obtaining a percentage value of 87.7% in the "Very High" criterion.